Fabrication of Gastroretentive Tablets of Rifaximin for Twice a Day Dosing Using Quality by Design Approach - A. Patel, Chandni; K. Shelat, Pragna; N. Lalwani, Anita (Drug Delivery Letters, 2015)
The purpose was to develop monolithic gastroretentive system of rifaximin for prolonged release. Rifaximin (RFX) is a semi-synthetic antibiotic used in traveller's diarrhea and its local effect in stomach is desirable. A target quality product was defined and mucoadhesive strength, floating lag time and % drug release at three different time points were identified as critical quality attributes. Hydroxypropyl methylcellulose K100M (HPMC), sodium carboxymethylcellulose (SCMC) and sodium bicarbonate were identified as critical factors affecting the selected attributes based on initial screening. Drug-excipient compatibility was established using Fourier transform infrared spectroscopy (FT-IR). A three factor, three levels Box-Behnken design was used to obtain the design space and the desirable zone where all the set criteria for the formulation are met. Tablets of all the design point batches were studied for physical properties, floating lag time, total floating duration, ex vivo mucoadhesion and in vitro drug release. The robustness of the formulation in the desirable zone was established by preparing check point batch. The composition that had highest desirability was identified and studied further. The water uptake and erosion behaviour of the tablet was determined and correlated with percentage drug release. Antimicrobial study was performed to gauge the inhibitory effect of the developed formulation. The release mechanism was found to be of anomalous or non-fickian type. Stability study was performed at the conditions recommended by ICH guidelines and it was found that the values of critical responses did not change during the duration of stability study. RFX gastroretentive delivery system for twice a day dosing could be developed.
Keywords: mucoadhesion